Pengembangan Perangkat Pembelajaran Berbasis Masalah Dengan Bantuan Geogebra Pada Materi Lingkaran Kelas VI SD (Universitas Dr. Soetomo, 2024)
Abstract Teachers can teach students about circle material by implementing problem-based learning using learning tools because it can make solving mathematical problems easier for students. The tools developed are Learning Implementation Plans (RPP), Student Worksheets (LKS), and Learning Outcome Tests (THB) which can be used by teachers in teaching material to a circle of students. This device is applied in learning activities to determine differences in learning outcomes before and after using the learning device. This research is development research with the research subjects namely class VI students. The instruments of this research are tests, response questionnaires, validation sheets, and observation sheets. The data analysis methods used to develop the tools uses analysis of assessing the validity of learning tools, data analysis of the teachers’ ability to manage learning, analysis of student activity data, analysis of student response questionnaire data and analysis THB data analysis. Meanwhile, to see differences in learning outcomes, use the t-test. The results of this research show that problem-based learning tools with the help of GeoGebra in circle material meet the criteria of being valid, practical, and effective. The results of the paired sample t-test using R-studio stated that there were differences in student learning outcomes before and after implementing the problem-based learning model with the help of GeoGebra in circle material. Keywords: GeoGebra, Learning Media, Problem Based Learning. Abstrak Guru dapat mengajarkan siswa tentang materi lingkaran dengan menerapkan pembelajaran berbasis masalah menggunakan perangkat pembelajaran karena dapat memudahkan penyelesaian masalah matematika bagi siswa. Perangkat yang dikembangkan berupa Rencana Pelaksanaan Pembelajaran (RPP), Lembar Kerja Siswa (LKS), dan Tes Hasil Belajar (THB) yang dapat digunakan guru dalam mengajarkan materi lingkaran kepada siswa. Perangkat tersebut diterapkan dalam kegiatan pembelajaran untuk mengetahui perbedaan hasil belajar sebelum dan setelah menggunakan perangkat pembelajaran. Penelitian ini merupakan penelitian pengembangan dengan subjek penelitian yaitu siswa kelas VI. Instrumen penelitian ini adalah tes, angket respon, lembar validasi, dan lembar observasi. Metode analisis data yang digunakan untuk mengembangkan perangkat menggunakan analisis penilaian validitas perangkat pembelajaran, analisis data kemampuan guru mengelola pembelajaran, analisis data aktivitas siswa, analisis data angket respon siswa dan analisis data THB. Sedangkan untuk melihat perbedaan hasil belajar menggunakan uji-t. Hasil penelitian ini menunjukkan bahwa perangkat pembelajaran berbasis masalah dengan bantuan GeoGebra pada materi lingkaran memenuhi kriteria valid, praktis dan efektif. Adapun hasil uji paired sample t-test menggunakan R-studio menyatakan bahwa terdapat perbedaan hasil belajar siswa sebelum dan sesudah menerapkan model pembelajaran berbasis masalah dengan bantuan GeoGebra pada materi lingkaran. Kata Kunci: GeoGebra, Perangkat Pembelajaran, Pembelajaran Berbasis Masalah.